Dragons in the mist: three new species of Pseudocalotes Fitzinger (Squamata: Agamidae) from the sky island archipelago of Peninsular Malaysia - Grismer, L. Lee; Quah, Evan S. H.; Wood, Perry L. Jr.; Anuar, Shahrul; Muin, Abdul; Davis, Hayden R.; Murdoch, Matthew L.; Grismer, Jesse L.; Cota, Michael; Cobos, Anthony J. (Zootaxa, 2016)
An integrative taxonomic analysis is used to delimit and describe three new species of Pseudocalotoes from the sky island archipelago of the Banjaran (=mountain range) Titiwangsa of Peninsular Malaysia. Pseudocalotes drogon sp. nov., from Fraser’s Hill, Pahang is basal to the sister species P. larutensis from Bukit Larut, Perak in the Banjaran Bintang and the new species P. rhaegal sp. nov. from Cameron Highlands, Pahang. Pseudocalotes drogon sp. nov. is differentiated from all other species of Psuedocalotes by having the combination of a flat rostrum; seven postrostrals; an interparietal; 11 circumorbitals; five canthals; 7–10 superciliaries; one scale between the rostral and nasal; nine supralabials; eight infralabials; 10 postnasal-suborbital scales; four postmentals; five or six sublabials; five or six chinshields; 47 smooth, wide, gular scales; weak transverse gular and antehumeral folds; two enlarged scales between the ear and eye; enlarged upper and lower posttemporals; a single enlarged supratympanic; no enlarged postrictals; three large scales bordering the dorsal margin of the ear opening; large pretympanic scales; eight scales in the nuchal crest not separated by a gap; enlarged vertebral scales extending to the tip of the tail; keeled and non-plate-like scales on flanks; 51 midbody scales; midventrals smaller than dorsals; 19 subdigital lamellae on the fourth finger; 23 subdigital lamellae on the fourth toe; preaxial scales on third toe enlarged and spinose; subdigital lamellae not unicarinate; HW/HL 0.52; HL/SVL 0.31; no elbow or knee patches; and a male dewlap color of lime-green bearing a central yellow spot. Pseudocalotes rhaegal sp. nov. is differentiated from all other Psuedocalotes by having the combination of a convex rostrum; 6–8 postrostrals; an interparietal; nine or 10 circumorbitals; five canthals; 7–10 superciliaries; one or two scales between the rostral and nasal scales; eight or nine supralabials; seven or eight infralabials; 11 or 12 postnasal-suborbital scales; four postmentals; four or five chinshields; 40–45 smooth, wide, gular scales; no transverse gular fold; a weak antehumeral fold; three or four enlarged scales between the ear and eye; an enlarged upper and lower posttemporal; an enlarged supratympanic; no enlarged postrictals; no large scales bordering the upper margin of the ear opening or in the pretympanic region; 6–8 enlarged nuchal crest scales not separated by a gap; enlarged vertebral scales extending to the base of the tail; weakly keeled, non-plate-like scales on the flanks; 52–58 midbody scales; midventrals smaller than dorsals; 19–21 subdigital lamellae on the fourth finger; 22–26 subdigital lamellae on the fourth toe; preaxial scales on the third enlarged and rounded; subdigital lamellae not unicarinate; HW/HL 0.50–0.54; HL/SVL 0.28–0.30; no elbow or knee patches; and female dewlap color yellow bearing a purple base. The analyses also indicated that the new species, P. viserion sp. nov. from Genting Highlands, Pahang in the southern section of the Banjaran Titiwangsa is the sister species of P. flavigula from Cameron Highlands 121 km to the north and can be separated from all other species of Psuedocalotes by having the combination of three postrostrals; 10 circumorbitals; four or five canthals; 5–7 superciliaries; rostral and nasals in contact; supralabials contacting the nasal; six or seven supralabials; six or seven infralabials; two or three postmentals; 47 or 48 smooth, flat, gular scales; three chinshields; weak transverse gular and antehumeral folds; two enlarged scales between the ear and eye; an enlarged upper and lower posttemporal; an enlarged supratympanic; no enlarged postrictals; 7–9 nuchal crest scales lacking gaps and not extending beyond midbody; weakly keeled and plate-like scales on the flanks; 35–38 midbody scales; ventrals smaller than dorsals; 22 or 23 subdigital lamellae on the fourth finger; 26 or 27 subdigital lamellae on the fourth toe; preaxial scales on the third toe not modified; subdigital scales not unicarinate; HW/HL 0.62; no white marking below the eye; dewlap in males yellow; and no elbow or knee patches. Pseudocalotes rhaegal sp. nov. most likely occurs in syntopy with P. flavigula in Tanah Rata at Cameron Highlands and its discovery adds to a growing body of literature detailing the recent descriptions of several new, upland, closely related, sympatric species in Peninsular Malaysia. Another new population referred to here as Pseudocalotes sp. nov. from the Hala-Bala Wildlife Sanctuary, Betong District, Yala Province, Thailand is discussed. The discovery and description of these three new Pseudocalotes from the upland regions of Peninsular Malaysia continues to underscore the remarkably high herpetological diversity and ecological complexity in this sky island archipelago that is still underestimated, unappreciated, and unprotected.